2018
DOI: 10.17126/joralres.2018.074
|View full text |Cite
|
Sign up to set email alerts
|

What do people do before going to the dentist? Qualitative study of cultural practices of pain relief in primary care.

Abstract: What do people do before going to the dentist? Qualitative study of cultural practices of pain relief in primary care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…7,8, 13 We understand in this context that people tend to solve the challenges of dental care that public health policies face with their own cognitive resources, attitudes, and cultural practices. 10 Within the limitations of the study, we report that no relationships were established between representations of dental health and social determinants, which could have helped to understand the importance of context in this area in greater depth. Despite this, the study achieves a broad approach, with a significant sample, to the representations of dental health in vulnerable sectors.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…7,8, 13 We understand in this context that people tend to solve the challenges of dental care that public health policies face with their own cognitive resources, attitudes, and cultural practices. 10 Within the limitations of the study, we report that no relationships were established between representations of dental health and social determinants, which could have helped to understand the importance of context in this area in greater depth. Despite this, the study achieves a broad approach, with a significant sample, to the representations of dental health in vulnerable sectors.…”
Section: Discussionmentioning
confidence: 83%
“…14,17,19 Dental trauma or fractured teeth would be less reported. 10 The studies also agree on the psychosocial importance -emotional, social, self-esteem, and labor insertion-that periodontal problems have for the population. 7,11,17,21, 22 It is observed that, although the reviewed bibliographical studies have examined the general theme of social representations of dental health, the specific objective of this study regarding the representation of the healthy and diseased mouth in vulnerable populations from a cultural approach could provide an innovative perspective.…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…Subsequently, the references of the included studies were manually searched for relevant articles, but none were identified. The reasons for excluding articles were: the study design (qualitative study and review studies) [8][9][10][11] , the study did not analyze the relationship between self-medication and toothache [12][13][14][15] , the participants were not adults 16,17 , did not specify the number of participants using antibiotics for the specified outcome 18 . For more information, visit: http://www.prisma-statement.org/…”
Section: Selected Studiesmentioning
confidence: 99%
“…A previous study showed it is common for patients to use alternative practices to alleviate toothache; these practices include the use of chemical products such as hydrogen peroxide, battery acid, gasoline, massages, ice, heat, coffee, cloves, and extracting the affected tooth [ 8 ]. It had been concluded that self-care strategies have palliative effects until professional dental care is possible [ 9 ].…”
Section: Introductionmentioning
confidence: 99%